2013
DOI: 10.1016/j.visres.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to synchronicity of biological motion in normal and amblyopic vision

Abstract: Amblyopia is a developmental disorder of spatial vision that results from abnormal early visual experience usually due to the presence of strabismus, anisometropia, or both strabismus and anisometropia. Amblyopia results in a range of visual deficits that cannot be corrected by optics because the deficits reflect neural abnormalities. Biological motion refers to the motion patterns of living organisms, and is normally displayed as points of lights positioned at the major joints of the body. In this experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(94 reference statements)
1
3
0
Order By: Relevance
“…Similarly to the case of normal ageing, the deficit in symmetry detection observed in the amblyopic participants may be a manifestation of a broader deficit related to suboptimal high-level visual processing. In line with this, recent evidence has shown that amblyopic individuals require more samples in both eyes to detect biological motion compared to normal control observers [32]. These threshold differences did not depend on low-level losses, but likely reflected losses in feature integration due to undersampling in the amblyopic visual system.…”
Section: Visual Symmetry Detection In Individuals With Impaired Binocsupporting
confidence: 70%
“…Similarly to the case of normal ageing, the deficit in symmetry detection observed in the amblyopic participants may be a manifestation of a broader deficit related to suboptimal high-level visual processing. In line with this, recent evidence has shown that amblyopic individuals require more samples in both eyes to detect biological motion compared to normal control observers [32]. These threshold differences did not depend on low-level losses, but likely reflected losses in feature integration due to undersampling in the amblyopic visual system.…”
Section: Visual Symmetry Detection In Individuals With Impaired Binocsupporting
confidence: 70%
“…The amblyopic eyes did exhibit elevated thresholds relative to fellow eyes and controls, but that was attributed to a greater sensitivity to the presence of noise dots rather than a selective impairment in biological motion processing (Thompson et al, 2008 ). Using a different task in which difficulty was controlled by removing dots from the point light displays, instead of adding noise, Luu and Levi ( 2013 ) recently demonstrated similar effects in observers with strabismic and anisometropic amblyopia. Observers had to decide whether two point light stimuli representing two dancers were moving in or out of synchrony with one another.…”
Section: Specific Cases Of Motion Integration: Biological Motion and mentioning
confidence: 97%
“…Although amblyopic eyes did exhibit elevated thresholds relative to fellow eyes and controls, this could be attributed to a greater sensitivity to the presence of noise dots rather than a selective impairment in biological motion processing ( Thompson et al, 2008b ). Recently, Luu and Levi (2013) used a different approach to assess biological motion perception in observers with strabismic and anisometropic amblyopia. They presented point light stimuli representing two dancers and the observers had to decide whether the dancers were moving in or out of synchrony with one another.…”
Section: Global Deficits In Amblyopiamentioning
confidence: 99%